Integrating Islamic Values into the Management of Waqf for the Sustainability of Islamic Education - Maskur Yusuf; Muhammad Alqadri Burga; Muhammad Firmansyah (Pascasarjana Universitas KH. Abdul Chalim, 2026)
Productive waqf management has emerged as a strategic mechanism to bolster the financial sustainability of Islamic educational institutions amid growing competitive and global pressures. This study aims to examine how Islamic values are integrated into the management of productive waqf and how such integration contributes to institutional self-reliance. Employing a qualitative case study design, data were collected from selected Islamic educational institutions that actively manage productive waqf through in-depth interviews, participant observation, and document analysis. Data were analyzed using an interactive model adapted from Miles, Huberman, and Saldaña, encompassing data condensation, display, and conclusion drawing. Findings indicate that core Islamic values amanah (trustworthiness), ‘adl (justice), ikhlas (sincerity), and mas’uliyyah (responsibility) are systematically embedded across planning, implementation, and evaluation phases of waqf projects. These values function as ethical mechanisms that enhance transparency, professionalism, and public trust, thereby reinforcing institutions’ financial resilience and social legitimacy. Enablers of value integration included religio-centric leadership, sharia-compliant regulatory frameworks, and organizational cultures rooted in religious commitment; primary barriers comprised uneven managerial capacity, limited public literacy on waqf, and insufficient digitalization of management systems. The study proposes an integrative conceptual model that synthesizes spiritual, ethical, and professional dimensions of productive waqf governance. Implications for practice include targeted capacity building for nazhir (waqf managers), adoption of digital reporting systems, and public literacy programs to maximize waqf impact. This research contributes empirically and conceptually to the literature on Islamic philanthropic governance and offers actionable recommendations for policymakers and practitioners.